2015
DOI: 10.2147/ott.s92109
|View full text |Cite
|
Sign up to set email alerts
|

Use of taxane-containing induction chemotherapy in combination with concurrent chemoradiotherapy in Chinese patients with locally advanced nasopharyngeal carcinoma: a meta-analysis

Abstract: PurposeTaxane-containing induction chemotherapy (IC) regimens in combination with concurrent chemoradiotherapy (CCRT) have been compared with non-taxane-containing IC combined with CCRT in randomized controlled trials (RCTs) in Chinese patients with advanced nasopharyngeal carcinoma (NPC). This meta-analysis aimed to systematically evaluate their clinical efficacy and safety profiling in this ethnic population.MethodsThe electronic databases, PubMed, Embase, MEDLINE, and Chinese Biomedical Database, were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Furthermore, a randomised phase III trial (NCT00003888) published in The New England Journal of Medicine, reported that induction chemotherapy with cisplatin, 5-FU plus docetaxel (TPF), was comparable to the regimen of cisplatin and 5-FU (PF), but significantly improved PFS and OS in patients with locoregionally advanced head and neck cancers 20 . Taxane-containing induction chemotherapy improved the treatment outcomes equally in patients with locally advanced NPC compared with the non-taxane chemotherapy 6 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a randomised phase III trial (NCT00003888) published in The New England Journal of Medicine, reported that induction chemotherapy with cisplatin, 5-FU plus docetaxel (TPF), was comparable to the regimen of cisplatin and 5-FU (PF), but significantly improved PFS and OS in patients with locoregionally advanced head and neck cancers 20 . Taxane-containing induction chemotherapy improved the treatment outcomes equally in patients with locally advanced NPC compared with the non-taxane chemotherapy 6 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with post-radiation squamous cell carcinoma (SCC) [1], radiation-induced sarcomas (RIS) of the head and neck following RT for NPC are even less common, with a crude incidence in adults of less than 0.5 % in various situations [15]. With improved patient survival [68], RIS is likely to be encountered more frequently. It is now generally believed that complete surgical resection of RIS provides the only chance of a cure [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of induction therapy may therefore affect patient survival and prognosis [25]. It was reported that induction therapy with taxanes significantly increases ORR (OR = 4.57, 95%CI 1.14–18.30, P = 0.032, z = 2.15) [26] compared with the non-taxane regimen. However, in this study, induction therapy with NPF had higher RR in lymph node lesions (81.0% vs 60%) compared with DPF.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse reactions caused by induction chemotherapy, especially increased systemic toxicity, hamper the application of induction chemotherapy and follow-up concurrent radiochemotherapy to a certain extent. It was reported that the incidence of grade 3–4 neutropenia in taxane-based induction therapy is significantly higher than that of non-taxane containing regimens (39.1% vs 16.1%, OR = 3.62, 95%CI 2.42–5.40, P < 0.001, z = 6.29) [26]. The incidence rates of neutropenia and stomatitis were 42 and 41%, respectively, after addition of the DPF regimen based on CCRT, which affected compliance with IC and subsequent CCRT.…”
Section: Discussionmentioning
confidence: 99%